2010
DOI: 10.1021/ol100266u
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Catalysis at the Crossroads: Cobalt-Catalyzed Alder−Ene Reaction versus [2 + 2] Cycloaddition

Abstract: The application of bidentate phosphine ligands in cobalt-catalyzed transformations of cyclic alkenes such as cyclopentene and cycloheptene with internal alkynes led to a chemoselective Alder-ene or a [2 + 2] cycloaddition reaction depending on the electronic nature of the alkyne and the bite angle of the ligand used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…[1][2][3][4] Recent examples of low temperature hydrocarbon transformations mediated by homogeneous cobalt catalysts include hydrogenation [5,6] (with enantioselective variants reported), C-C bond formation,[4, 7,8] C-H functionalization, [3,[9][10][11] and cycloaddition reactions. [12] These reactions occur at quite mild temperatures and are the thermodynamically exergonic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Recent examples of low temperature hydrocarbon transformations mediated by homogeneous cobalt catalysts include hydrogenation [5,6] (with enantioselective variants reported), C-C bond formation,[4, 7,8] C-H functionalization, [3,[9][10][11] and cycloaddition reactions. [12] These reactions occur at quite mild temperatures and are the thermodynamically exergonic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Hilt et al. also reported that less‐strained cyclopentene has an interim reactivity between simple alkenes and norbornenes, affording both cyclobutene and 1,4‐diene 8. However, the chemoselectivity mainly depends on the structural nature of the alkenes.…”
Section: Methodsmentioning
confidence: 99%
“…strained cyclopentene has an interim reactivity between simple alkenes and norbornenes, affording both cyclobutene and 1,4-diene. [8] However, the chemoselectivity mainly depends on the structural nature of the alkenes. Therefore, it is a challenge to develop a transformation that can provide previously inaccessible products beyond conventional reactivity.…”
mentioning
confidence: 99%
“…However, it has been noted that the direction of the catalytic reactions often depends on the structure of the phosphine ligand. Major research on these ligand-controlled reactions has been made by the groups of Hilt and Cheng, in particular, on the selective formation of meta / para -products of Diels–Alder reactions [2832], linear/branched products of hydrovinylation reactions [3334], [2 + 2] cycloadditions vs Alder-ene reactions [35], E / Z isomerizations of alkenes [3637] and other processes [3842]. …”
Section: Introductionmentioning
confidence: 99%